2021
DOI: 10.4103/jfmpc.jfmpc_1996_20
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of patients presenting to the emergency department with upper gastrointestinal bleeding

Abstract: Background: Upper gastrointestinal (UGI) bleeding is a common presentation to the Emergency Department (ED), and is associated with re-bleeding and significant mortality. Although several studies have described etiology and outcome of UGI bleeding, few have been done in the EDs. Materials and Methods: This prospective observational cohort study included all patients presenting with hematemesis or melena, between June 2016 and January 2017 to the ED. Demographic data, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…A cross-sectional study carried out by Surendran M et al at a tertiary care hospital in southern India found that males (107;77.5%) outnumbered females (31;22.5%) with an average age of 53.5 ± 13.17 years [ 9 ]. Similar results were reported by Shenoy V et al [ 10 ]. It is discernable from the above studies that UGIB is more prevalent in men than in women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A cross-sectional study carried out by Surendran M et al at a tertiary care hospital in southern India found that males (107;77.5%) outnumbered females (31;22.5%) with an average age of 53.5 ± 13.17 years [ 9 ]. Similar results were reported by Shenoy V et al [ 10 ]. It is discernable from the above studies that UGIB is more prevalent in men than in women.…”
Section: Discussionsupporting
confidence: 92%
“…Injections of epinephrine (1:10 000 dilution), injections of sclerosants such as 100% ethanol, thermal contact devices such as bipolar electrocoagulation probes or heater probes, and clips are recommended for bleeding ulcers. Shenoy V et al observed that PRBC transfusion was done in 46.7% cases whereas 37(26.6%) cases received PRBC transfusion in our study [ 10 ]. JP Hreinsson et al found that 60% of patients presented with UGIB required blood transfusion [ 21 ].…”
Section: Discussionmentioning
confidence: 56%
“…Etiological treatment and symptomatic treatment were performed simultaneously to impel the rehabilitation of patients and shorten the hospital stay [16]. Secondly, a systematic nursing model was established through the process of emergency evaluation-emergency treatment-comprehensive assessmentclinical treatment-prognostic assessment [17], the reliability of diagnosis and treatment was increased, missed diagnosis and misdiagnosis were reduced, and the danger of life in patients due to rebleeding was reduced [18].…”
Section: The Nursing Model Based On Rockall Scoring System Can Facili...mentioning
confidence: 99%